HUBUNGAN ASPEK KOGNITIF PASANGAN USIA SUBUR (PUS) TERHADAP PENGGUNAAN ALAT KONTRASEPSI - Kusumawardani, Emi; Multazam, Andi Muhammad; Safitry, Rusni; Lestyani, Lestyani; Arini, Ketut Novia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Contraception is an effort made to regulate the number and spacing of pregnancies using various contraceptive methods available. Some factors that influence contraceptive selection are knowledge and attitudes by couples of childbearing age. Based on an initial survey conducted at the Sawah Lebar Health Center to 10 women of childbearing age, there were 6 PUS mothers who had good knowledge but had a negative attitude because they knew knowledge about contraception but did not participate in the family planning program and 4 PUS mothers had good knowledge and a positive attitude in choosing contraception. The purpose of the study was to determine the relationship of cognitive aspects of couples of childbearing age (PUS) to the use of contraceptives. The research method used quantitative research with a cross sectional design. The research was conducted at the Sawah Lebar Health Center. The research was conducted in December 2023. The population was the mother of childbearing age couples (PUS) aged 20-37 years who were at the Sawah Health Center which amounted to 4,884 people. The sample amounted to 103 people. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed a relationship between knowledge p value 0.000 and attitude p value 0.000 to the use of contraceptives. It is recommended that the Puskesmas be more active and more informative in socializing family planning. So that public knowledge and public awareness about family planning will increase so that the use of contraceptives is also getting better.Keywords: Contraception, childbearing age couples, knowledge, attitude.